Faktor-Faktor yang Mempengaruhi Produktivitas Tenaga Kerja Pemanen Kelapa Sawit di PTPN IV Ngabang Kabupaten Landak - Robertus Romi; Josua Parulian Hutajulu; Maswadi Maswadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Oil palm (Elaeis guineensis) is a major tropical commodity in Southeast Asia that plays an important role in the global economy, especially as a raw material for the food, cosmetics, and bioenergy industries. West Kalimantan Province is one of the regions with the largest oil palm plantations in Indonesia, where its area increased from 1,166,282 Ha in 2020 to 1,449,274 Ha in 2022. Landak Regency contributes 119,326 Ha, but its productivity is still relatively low with a total production of 184,592 tons or around 1.54 tons/Ha. PTPN IV Ngabang in Landak Regency as one of the largest palm oil companies in the area also faces the problem of low productivity, thus hindering harvest rotation and the achievement of daily targets. This study aims to describe the productivity of oil palm harvester labor and find out what factors affect the productivity of oil palm harvester labor in PTPN IV, Ngabang District, Landak Regency. The method uses qualitative as an approach in finding answers with a sample of 78 respondents. The variables in this case study are labor productivity (Y) and independent/independent variables (X), namely age, working period, family dependents, mileage, and education. The data analysis technique used in this case study is analysis on multiple linear regression. The results of the study concluded that the productivity of oil palm harvesters in PTPN IV Ngabang averaged 1200,71 kg/day. Simultaneously, age, family dependents, working period, mileage, and education affect the productivity of oil palm harvester labor at PTPN IV Ngabang. Partially, the factor that greatly affects the productivity of the oil palm harvester workforce at PTPN IV Ngabang is the age factor of the worker and working period. Meanwhile, the factors of family dependents, distance traveled and labor education partially did not have a significant effect.